Choice or control: what do patients really want? - O’Neill, Liam (Annals of Research Hospitals; Vol 1 (April 2017): Annals of Research Hospital, 2017)
When it comes to selecting a health care provider, patients want choice. Gone are the days when patients were willing to accept a passive role in their own care (1). There is also a strong demand for comparative information on the quality of health care providers, such as reports on risk-adjusted outcomes or patient satisfaction. Given that many patients now have access to such information, one would think that “quality compare websites” would play a significant role in patient decision-making. Yet research has found that no more than about 5% of patients actually use such information when choosing a health care provider (2).